ANALISIS PENGARUH LINGKUNGAN BELAJAR VIRTUAL DAN MOTIVASI PESERTA TERHADAP PEMAHAMAN PESERTA TRAINING - Agnes Syifa’ Aulia; Nuraedhi Apriyanto; Bayu Ariwibowo; Rangga Dino Alfian (Ivet University, 2025)
This research aims to analyze the influence of the virtual learning environment and participant motivation on their understanding of the New Model Training material at the Astra Motor Training Center Semarang. After the global Covid-19 pandemic occurred, many training and education shifted to virtual learning methods. However, challenges such as lack of face-to-face interaction and potential distractions in the home or work environment can affect participant motivation. This research method is quantitative using surveys of training participants. The results of the analysis show that the virtual learning environment, especially through the Zoom application, has a positive influence on participants' understanding of the training material. Apart from that, participants' motivation also had a significant positive correlation with their understanding. The combination of an effective virtual learning environment and high levels of motivation provides a significant positive impact on understanding the training material. Based on the results of the t test, the following data was obtained: the virtual learning environment variable obtained a significant value of 0.037, which is smaller than 0.05. So these results show the influence of the virtual learning environment on the understanding of New Model Training participants at the Astra Motor Training Center Semarang and the learning motivation variable obtained a significant value of 0.002, which is smaller than 0.05. So these results show the influence of learning motivation on the understanding of New Model Training participants at AMTC Semarang. In conclusion, in the context of the New Model Training at AMTC Semarang, the virtual learning environment has a presentation of 3.8% and participant motivation has a presentation of 9.3% are important factors that are interrelated in increasing participants' understanding of the New Model Training material.